Evaluating the impacts of cellphone use policies on cellphone-distracted fatal crashes - Gupta, Nischal; Megat-Johari, Megat Usamah; Megat-Johari, Nusayba (Elsevier, 2025)
Introduction: Driver distraction is becoming increasingly frequent while driving, with a notable portion of traffic crashes linked to distraction, often due to cellphone use. States have enacted varying levels of policies, including partial and full handheld bans, texting bans, and their combinations to target distracted driving. Existing research is limited in terms of both geographical area and time period, and do not account for whether cellphone distraction contributed directly to crash incidents. This study compares state-level monthly fatal crashes involving cellphone distraction in the United States between 2011 and 2021. Method: A two-way random effects negative binomial model was estimated to compare trends in cellphone-distracted fatal crashes as a function of the type of cellphone use policy and time passed since the enactment of the law while controlling for other factors. Results: The results showed that handheld bans were negatively correlated with cellphone-distracted fatal crashes, while texting bans alone were positively correlated with crashes. A more comprehensive ban on handheld and texting resulted in the greatest safety benefit. Interestingly, the effectiveness of both the texting ban and handheld ban was found to taper off after two years of implementation. Conclusions: The study highlights the importance of comprehensive cellphone bans in improving road safety by effectively reducing cellphone-distracted fatal crashes. The state-specific random effects indicate systematic differences in crash rates across states. The study also highlights the need for sustained policy reinforcement to offset the diminishing effectiveness of these bans. Practical applications: The findings highlight the effectiveness of comprehensive cellphone bans in reducing distracted fatal crashes and encourage states without such policies to adopt them. States with higher crash rates identified through state-specific effects may require enhanced enforcement and tailored interventions. Targeted seasonal enforcement and sustained awareness campaigns are crucial for maintaining the long-term effectiveness of cellphone bans.